International Trade and Management of Shared Renewable Resource - Yasuhiro Takarada; Takeshi Ogawa; Weijia Dong (European Regional Science Association (ERSA), 2012)
This paper examines the effects of international trade and resource management in a two-country model where each country controls domestic harvest to prevent over-exploitation of an internationally shared renewable resource (e.g., fishery resources). We show that contrary to conventional wisdom, an opening up of trade is likely to raise the steady state utility of a resource-good exporting country, even if it implements weak resource management standards, because the expansion of the resource sector which enjoys economic rent increases its total income. To maximize world welfare in a trading steady state, a resource-good importing country should implement stricter resource management after trade than under autarky but it will implement weak resource management to enjoy economic rent by mitigating the contraction of the resource sector (i.e., rent shifting). Thus, a resource-good exporting country should give some side payments to give a resource-good importing country an incentive to implement strict resource management standards.
Keywords: F11; Q27; 330; Gains from trade; Shared renewable resource; Resource management